Research on the Hydroelasto-Plasticity Method and Its Application in Collapse Analyses of Ship Structures - Qingning Yuan; Zhiyong Pei; Ye Zhu (Journal of Marine Science and Engineering)
The prevailing trend in marine engineering towards large-scale ship design inherently reduces structural rigidity, amplifying fluid–structure interaction effects during extreme wave loading scenarios. Conventional ultimate strength assessment frameworks fail to account for such dynamic coupling mechanisms. To address this critical limitation, this study proposes a novel hydroelasto-plastic coupling framework and establishes time-dependent coupling equations governing fluid–structure interactions through systematic integration of the hydrodynamic principle and structural dynamics principle. Through a co-simulation approach combining computational fluid dynamics and finite element methods, the pressure and displacement boundary conditions at the fluid–structure interface are iteratively exchanged; thus, the time-domain solution of the coupling equations is obtained. A simplified box-type structure is analyzed to investigate its hydroelasto-plastic behavior and the mechanism of fluid–structure interaction. This research facilitates the elucidation of progressive collapse characteristics in ship hull structures under hydrodynamic loads, demonstrating significant implications for structural safety design.